Intersectionality and urban mobility: A systematic review on gender differences in active transport uptake. (March 2023) - Yuan, Yue; Masud, Manal; Chan, Herbert; Chan, Wency; Brubacher, Jeffrey R.
Abstract: Background: Active transport has numerous environmental and health benefits. However, these benefits are not evenly distributed across the population because its utilization is strongly linked to a person's socioeconomic and cultural factors. Through the lens of intersectionality, this systematic review analyzed how gender and its interactions with other socioeconomic and cultural factors influence a person's decision to utilize active transport in urban settings. Methods: Following the PRISMA guidelines, the authors screened 1, 993 titles and abstracts that were published between January 2000 and December 2021. Twenty-one articles were included for data extraction and synthesis. Results: A person's decision to walk or cycle is highly contextual. In general, women with lower socioeconomic status tend to walk more out of necessity. Women with higher socioeconomic status, higher education level, more free time, and access to safe and convenient infrastructure tend to cycle more. Gendered social and cultural factors might also deter some women from active transport. The following recommendations may attract more people to walk or cycle for transportation: developing community-based programs that empower girls and women to cycle; building a safe environment that protects all vulnerable road users; creating media and social marketing campaigns that shift the cultural narratives around active transport; designing neighourhoods with higher mixed land usage; and advocating for gender and income equality. Highlights: This is the first systematic review that analyzes how intersectionality affects urban mobility. Factors including socioeconomic status, education level and built environment influence a person's decision to walk or cycle. Gendered social and cultural norms may further deter women from using active transport.